Proceedings of the 2018 3rd International Conference on Modelling, Simulation and Applied Mathematics (MSAM 2018) 2018
DOI: 10.2991/msam-18.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Model of Spare Parts Optimization Based on GA for Equipment

Abstract: Combined with the engineering requirements for the optimal allocation of the current ammunition equipment spare parts, a spare part optimization model based on genetic algorithm was established. With the combination of good readiness and cost of ammunition equipment, the use of genetic algorithm had the characteristics of fast convergence, strong global optimization, and simple programming. The model was solved and the spare parts of ammunition equipment were optimally configured. Finally, an example of ammuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, the reliability theory does not reflect sufficiently the problem of combat damage restoration with use of special spare parts kits. Today, there are a lot of studies related to problems of technical systems supply with spare parts [1][2][3][4][5][6][7][8][9].…”
Section: Definition Of Research Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the reliability theory does not reflect sufficiently the problem of combat damage restoration with use of special spare parts kits. Today, there are a lot of studies related to problems of technical systems supply with spare parts [1][2][3][4][5][6][7][8][9].…”
Section: Definition Of Research Problemmentioning
confidence: 99%
“…In [3], we proposed the genetic algorithm for spare parts optimization. We demonstrated that in some cases the use of genetic algorithm permits to solve optimization tasks.…”
Section: Definition Of Research Problemmentioning
confidence: 99%
See 2 more Smart Citations